Design and Implementation of a Vlsm Simulator - Hussein Abdul-Razzaq Lafta; Ammar Osamah Hoori (Journal of Engineering, 2023)
Variable-Length Subnet Masks (VLSM), often referred to as "subnetting a subnet", is used to maximize addressing efficiency. The network administrator is able to use a long mask on networks with few hosts, and a short mask on subnets with many hosts. This addressing scheme allows growth and does not involve wasting addresses. VLSM gives a way of subnetting a network with minimal loses of IP addresses for a specific range. Unfortunately, the network administrator has to perform several mathematical steps (or use charts) to get the required results from VLSM. In this paper, a simple graph simulator is proposed (using Visual Basic 6.0 Language) to perform all the required mathematical steps and to display the obtained required information (the subnet ID, broadcast ID, usable addresses for sub networks and others). The simulator also includes the ability to draw a suggested network topology that matches the entries. The implementation of the simulation required only very few entries (IP, prefix and number of subnets).This simulator is useful for students, instructors, and network engineers to analysis and design a VLSM network by providing all required information in simple, fast and easy steps. Moreover, the software draws a full detailed suggested network topology which is considered a helpful tool for the network administrator that he should have.